2018
DOI: 10.1080/17474124.2018.1441711
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal hiatal hernia: risk, diagnosis and management

Abstract: Esophageal hiatal hernia involves abnormal abdominal entry into thoracic cavity. It is classified based on orientation between esophageal junction and diaphragm. Sliding hiatal hernia (Type-I) comprises the most frequent category, emanating from right crus of diaphragm. Type-II esophageal hernia engages both left and right muscular crura. Type-III and IV additionally include the left crus. Age and increased body mass index are key risk factors, and congenital skeletal aberrations trigger pathogenesis through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 83 publications
0
50
0
4
Order By: Relevance
“…Esophagectomy is associated with postoperative morbidity; by contrast, minimally invasive laparoscopy affords better visualization of the hernia and entails fewer postoperative complications. 1,2 Allen et al 3 have described their observations in a case series wherein 119 of 147 patients with an intrathoracic stomach underwent surgery. They state that patients with an intrathoracic craniocaudal stomach who have obstructive symptoms at the initial presentation should undergo surgical repair and that elective surgery is both safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Esophagectomy is associated with postoperative morbidity; by contrast, minimally invasive laparoscopy affords better visualization of the hernia and entails fewer postoperative complications. 1,2 Allen et al 3 have described their observations in a case series wherein 119 of 147 patients with an intrathoracic stomach underwent surgery. They state that patients with an intrathoracic craniocaudal stomach who have obstructive symptoms at the initial presentation should undergo surgical repair and that elective surgery is both safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…According to Andolfi et al, esophageal manometry should be performed especially before undergoing surgery, as it can rule out achalasia or other motility disorders. Before performing fundoplication surgery it is also essential to verify the integrity of the peristaltis of the esophagus, which can be done using high resolution manometry (HRM) as it provides real time pressure recording [3,5]. However, placement of the manometry catheter can be rather difficult; Dallemagne et al have reported that the method is completed in less than 50% of cases [17].…”
Section: Diagnosis Of Esophageal Hiatal Herniamentioning
confidence: 99%
“…Usually, a Nissen fundoplication (360°) is performed after most hiatal hernia repairs, unless there is a preexisting esophageal dysmotility, in which case the Toupet fundoplication (270°) is preferred [15]. There has been recent evidence that a complete fundoplication might be more beneficial as it has a reduced abnormality in the pH profile and a stronger impact [3]. Laparoscopic surgery provides the advantages of a minimally invasive approach, which consist of: shorter hospital stays, faster time of recovery, reduced post-operative pain and reduced pulmonary complications [1,28].…”
Section: Treatment Of Hiatal Herniamentioning
confidence: 99%
See 2 more Smart Citations